Shoulder edge anterior adduction contracture in pediatric patients after burns: Anatomy and treatment: A new approach - Viktor M. Grishkevich; Max Grishkevich; Vasiliy A. Menzul (Elsevier, 2018)
Background: Burns of anterior shoulder joint surface and neighboring areas produce shoulder edge adduction contracture and scar deformity, slowing down the development of upper limbs in pediatric patients. Therefore, surgical reconstruction is indicated as early as the contracture is formed. Currently used surgical techniques, based on counter transposition of the local triangular flaps and skin transplants, do not solve the problem because of incomplete release of the contractures; repeated operations are often performed. The scar deformity also remains. Methods: The anatomy of shoulder edge scar adduction contractures was studied in 16 personally-operated pediatric patients before and during surgery. Being dissatisfied by outcomes from the skin graft and triangular flaps' use, we started involving the undamaged axillary tissue in the form of adipose-cutaneous whole layer in plasty to fully release the contracture and reduce the deformity of rough scars' excision. Results: Edge shoulder adduction contractures were caused by scars covering the joint's anterior flexion lateral (FL) surface and scars of lateral sheet of the crescent fold located along the anterior edge of axillary fossa. We pointed out that contracted scars were not restricted only by the fold, but spread from the fold's crest to the joint rotation axis and the contracture was caused by the surface deficit on all extent. After contracted scar dissection with Y-incision, wound's edges divergence and at the joint rotation axis wound (scar surface deficit) accepted a positive linear meaning that gives for deficit and wound a trapezoid form. Reconstruction consisted in contracture release on all its extent with a Y-incision, mobilization of axillary and neighboring tissues in a form of non-incised/whole adipose-cutaneous layer. According to whole flap/layer surface, the scars adjusting to wound/scar surface deficit were excised and the wound was covered with axillary tissue layer that was transposed with tension. Excellent functional outcomes and improved appearance of cosmetically important zone were achieved without complication and donor site morbidity. Conclusion: The presented new technique is simple, safe, and effective; it allows one to avoid skin transplants, as well as triangular and regional flaps use. These factors enable the authors to recommend a wider use of the axillary layer in pediatric practice for edge shoulder adduction contracture treatment. Keywords: Axilla contracture, Pediatric burns, Axilla reconstruction, Edge axillary contracture